Public-private partnership in the mineral resources sector of Russia: how to implement the classical model? - Sergei M. Lavlinskii; Artem A. Panin; Aleksandr V. Plyasunov (Zapiski Gornogo instituta (1999), 2025)
A comparative financial and economic analysis is conducted of different public-private partnership (PPP) models for industrial infrastructure construction projects in an underdeveloped resource-rich region. The Stackelberg game theory-based model is used to build a parametrized family of bilevel mathematical programming models that describe an entire spectrum of partnership schemes. This approach enables a comparison of different strategies for the distribution of infrastructure investments between the government and the subsoil user and hence a scenario of transformation of Russia’s current PPP scheme into the classical partnership model, which is practiced in developed economies. To this end, a database is created on fifty polymetallic deposits in Transbaikalia, and a comparative analysis is conducted of Stackelberg equilibrium development programs that implement different PPP models. The numerical experiment results show the classical PPP model to be most effective in the case of a budget deficit. The analysis helps assess the economic consequences of a gradual transformation of the partnership institution in industrial infrastructure construction from investor support in the Russian model to government support in the classical scheme. Intermediate partnership models, which act as a transitional institution, help reduce the budget burden. These models can be implemented by clustering the deposits, developing subsoil user consortia, and practicing shared construction of necessary transport and energy infrastructure. The intensification of horizontal connections between subsoil users creates favorable conditions for additional effects from the consolidation of resources and can serve as a foundation for a practical partnership scheme within the framework of the classical model.